Pengaruh Karakteristik Pekerjaan dan Budaya Kerja Terhadap Work Life Balance pada Karyawan Yoehan Busana Purwasukasi - Dina Nurlia Fajar; Enjang Suherman; Laras Ratu Khalida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study investigates the influence of job characteristics and work culture on work-life balance among Yoehan Busana Purwasukasi employees. The research method employed is a quantitative descriptive approach. This study's data collection method uses a questionnaire with a Likert measurement scale. The population in this study included 84 employees of Yoehan Busana Purwasukasi. In this study, sampling used Random Sampling with Slovin 5%, resulting in 69 samples for data analysis research—multiple Linear Regression Analysis Technique with a significance level of 0.05. The overall calculation of the analysis used the SPSS version 25 program. The results of the research revealed that (1) Partially Job Characteristics had a significant and positive impact on Work-Life Balance in Yoehan Busana Purwasukasi employees (2) Partially Work Culture had a significant and negative impact on Work-Life Balance in Yoehan Busana Purwasukasi employees (3) Simultaneously Job Characteristics and Work Culture have a significant and positive impact on Work-Life Balance for Yoehan Busana Purwasukasi employees.